Microstructure regulation and mechanical properties of Ti-34Nb-4Zr-0.3O alloys by aging - QI Huan; WU Xiangwei; ZHANG Hanya; CHEN Feng; WANG Yuhui; WANG Chunyang (Cailiao gongcheng, 2024)
Metastable β type Ti-34Nb-4Zr-0.3O(mass fraction/%)alloy (TNZO) was prepared by vacuum arc melting, single-phase hot forging and cold rolling. The cold-rolled TNZO alloys were aged at low-temperature of 250 ℃ and 300 ℃ in order to reveal the effect of aging temperature and time on the precipitation behavior of ω phase and the mechanical properties of the alloys. The results show that ω phase precipitates in nanometer size as a result of low temperature aging which leads to the increase of strength and elastic modulus of the alloys. ω phase is easy to coarsen and agglomerate when the alloy is aged at 300 ℃, which results in the rapid drop of the elongation and embrittlement of the alloy. Short time aging at 250 ℃ could make the ω phase precipitated dispersedly with small volume fraction, enabling the alloy to have excellent comprehensive properties of high strength, low modulus, ultra-high elasticity and good plasticity and show a broad application prospect in the field of aerospace elastic titanium alloys and medical implant titanium alloys.